An unusual presentation of breast tuberculosis: A case report. Issue 1 (11th November 2020) - Rizzo, Giovanna; Colli, Francesco; De Marco, Paolino; La Brocca, Antonella; Militello, Gabriella; Gulotta, Gaspare.
Abstract: Primary breast tuberculosis is an uncommon disease, especially in nonendemic areas. Its presentation could mimic a cancer or an abscess, but this entity must be considered for differential diagnosis in women coming from endemic countries. Abstract : Primary breast tuberculosis is an uncommon disease, especially in nonendemic areas. Its presentation could mimic a cancer or an abscess, but this entity must be considered for differential diagnosis in women coming from endemic countries.